Feasibility Study of Agile Manufacturing in Automobile Industry - Kannan, P; Sathya, J (Journal of Commerce and Trade, 2010)
Manufacturing industry may well be on the verge of a major paradigm shift. The emergence of firms producing at low-wage economies has quashed low price strategies for most European and American manufacturers. US manufacturing industries are realizing that global prominence in manufacturing can be achieved only through innovation and thus resulted in the birth of ‘Agile Manufacturing System’ in the 21st century. Agile manufacturing is the process of accomplishing the ability to successfully market low-cost, high quality products with short lead times that provide enhanced customer value through customization. A customer has to be treated as an individual asset. They expect low volume, high quality and require small quantities of highly custom, design-to-order products, and where additional services and value-added benefits like product upgrades and future reconfigurations are as important as the product itself. Ford, the leading automobile industry is paving a new dimension to Agile Manufacturing system. This paper throws light on feasibility of agile especially in automobile manufacturing sector.